Hubungan Penerapan Manajemen Berbasis Sekolah (MBS) dan Budaya Organisasi Terhadap Kinerja Guru di SMA Daar El Qolam - Ahmad Reza Aulia; Isti Rusdiyani; Cucu Atikah (Cakrawala Pedagogik, 2023)
This research discusses the low performance of teachers at SMA Daar el-Qolam, Gintung, Jayanti, Tangerang. The low performance is attributed to cultural organizational factors and the suboptimal implementation of school-based management. Therefore, this study explores the relationship between school-based management, organizational culture, and teacher performance at SMA Daar el-Qolam. The research design is quantitative and employs a correlational method. All data for this study were obtained through observation, documentation, and interviews, with a questionnaire as the research instrument. The population for this study consists of 95 teachers. The sample used in this study is a saturated sample, so the sample size is equal to the population size. Based on the research findings (1) There is a positive and significant relationship between the implementation of School-Based Management (SBM) and teacher performance at SMA Daar el-Qolam. This is evidenced by the percentage of the relationship between SBM and teacher performance variables, which is 41.60%, while the remaining 58.40% represents other unexplained factors in this study. (2) There is a positive and significant relationship between organizational culture and teacher performance at SMA Daar el-Qolam. The percentage of the relationship between organizational culture and teacher performance variables is 34.40%, while the remaining 65.60% is not explained in this study. (3) There is a significant combined relationship between the implementation of School-Based Management (SBM) and organizational culture with teacher performance at SMA Daar el-Qolam. The percentage of the variables SBM and Organizational Culture in explaining teacher performance variables is 52.60%, while the remaining 47.4% is unexplained. The R-value has been adjusted without any other factors included.